1998
DOI: 10.1099/0022-1317-79-12-2895
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of primary infection of a European human immunodeficiency virus type 1 clade B isolate in chimpanzees.

Abstract: The aim of the study was to select, from a panel of candidate European human immunodeficiency virus type 1 (HIV-1) clade B primary virus isolates, one isolate based on replication properties in chimpanzee peripheral blood mononuclear cells (PBMC). Secondly, to evaluate the in vivo kinetics of primary infection of the selected isolate at two different doses in two mature, outbred chimpanzees (Pan troglodytes). Four different low passage, human PBMC-cultured ' primary ' HIV-1 isolates with European clade B conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Despite the fact that most HIV-1 isolates have been shown to produce nonpathogenic infections in chimpanzees, continuing efforts have been made to find or derive an isolate of HIV-1 that is more pathogenic for this species (3,16,33,34). Recent findings suggest that chimpanzees are a natural reservoir for SIVcpz and may have served as the source of HIV-1 introduction into the human population (15).…”
mentioning
confidence: 99%
“…Despite the fact that most HIV-1 isolates have been shown to produce nonpathogenic infections in chimpanzees, continuing efforts have been made to find or derive an isolate of HIV-1 that is more pathogenic for this species (3,16,33,34). Recent findings suggest that chimpanzees are a natural reservoir for SIVcpz and may have served as the source of HIV-1 introduction into the human population (15).…”
mentioning
confidence: 99%
“…Experimental primate models of mucosal HIV infection have demonstrated that maximal levels of viral expression occur in different tissue compartments sequentially over short periods of time (22,24,25). Viral loads in blood, genital secretions (26,27), and other compartments peak at very high levels around 4 weeks after infection (27) and then decrease in association with the appearance of virus-specific CTL responses (4,28).…”
Section: The Biology Of Hiv Expansionmentioning
confidence: 99%
“…However, the HIV isolated from this individual is evidently an unusual mutant that evolved during the prolonged incubation period, as it rapidly produced an AIDS-like syndrome upon transfer to another chimpanzee. Despite many studies attempting to find the answer (for examples, see Arthur et al 1989;Gendelman et al 1991;Di Rienzo et al, 1994;Heeney et al 1995;Ehret et al 1996;Benton et al 1998;Bogers et al 1998;Pischinger et al 1998), the mystery remains -this retrovirus seems to live in a symbiotic state within the chimpanzee immune system, whereas it almost routinely destroys the helper T cells of humans. Although the evolutionary reason for this is now reasonably clear (chimpanzees are probably a natural reservoir and humans are not), the mechanistic explanation remains obscure.…”
mentioning
confidence: 99%